Estimation of Limiting Conditional Probabilities for Regularly Varying Time Series - Dimy Anguima Ibondzi, Herve (Université d'Ottawa / University of Ottawa, 2014)
In this thesis we are concerned with estimation of clustering probabilities for univariate heavy tailed time series. We employ functional convergence of a bivariate tail empirical process to conclude asymptotic normality of an estimator of the clustering probabilities. Theoretical results are illustrated by simulation studies.
Keywords: Conditional Probabilities